2010
DOI: 10.1089/thy.2010.1639
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the Autoimmune Polyglandular Syndrome Type 3 Variant

Abstract: AITD and T1D share common susceptibility gene variants that possibly act pleiotropically as risk factors for the development of autoimmunity in APS3v. The functional consequences of the genetic variants as well as their interactions should be explored in greater detail. In particular, the functional consequences of the variants of forkhead box P3 predisposing to APS3v need to be elucidated. Finally, further large-scale genome-wide associations studies of single-nucleotide polymorphism variations capturing many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 61 publications
1
41
0
1
Order By: Relevance
“…Pathological changes in HPT axis and impairment of its regulation can lead to several thyroid diseases, cardiovascular, and neurological disorders [3][4][5]. Thyroid dysfunctions can manifest as complications of some diseases, including type 1 diabetes mellitus (DM1) [6][7][8]. First data showing that thyroid diseases are much more common in patients with DM1 were obtained in the early 1980s [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological changes in HPT axis and impairment of its regulation can lead to several thyroid diseases, cardiovascular, and neurological disorders [3][4][5]. Thyroid dysfunctions can manifest as complications of some diseases, including type 1 diabetes mellitus (DM1) [6][7][8]. First data showing that thyroid diseases are much more common in patients with DM1 were obtained in the early 1980s [9,10].…”
mentioning
confidence: 99%
“…First data showing that thyroid diseases are much more common in patients with DM1 were obtained in the early 1980s [9,10]. Later, it was shown that about one third of patients with DM1 have autoimmune thyroid diseases, such as Graves' disease, Hashimoto's thyroiditis, and pospartum thyroiditis [6,8]. Historically, the functional link between DM1 and dysfunctions of HPT axis and the thyroid gland was studied giving preference to experi-…”
mentioning
confidence: 99%
“…With regard to the pathogenic mechanisms that contribute to the development of APS3v, there are several hypothetical mechanisms by which HLA could be involved in a common etiology of T1D and AITD (1,9). First, some HLA susceptibility alleles for T1D might be in tight linkage disequilibrium with that for AITD.…”
Section: Frequencies Of Antigen or Allele Controlmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1D) and autoimmune thyroid disease (AITD) are common autoimmune endocrine diseases, and the occurrence of both T1D and AITD in the same patient is defined as autoimmune polyglandular syndrome type 3 variant (APS3v) (1). Epidemiological evidence suggests that there are overlapping genetic backgrounds for APS3v (T1D and AITD).…”
Section: Introductionmentioning
confidence: 99%
“…The attack by auto-reactive T cells on the pancreas is the main immunological feature in T1DM. Deregulation of T cell homeostasis is a key event in the maintenance of self-tolerance breakdown in T1DM pathogenesis (Dittmar and Kahaly, 2010). The activation of the T cell surface receptor (TCR) triggers intracellular signaling cascades, which result in T cell activation, differentiation, and acquisition of effector function or apoptosis.…”
Section: Introductionmentioning
confidence: 99%